The Influence of Competency and Compensation on the Performance of the Kalimantan Regional PKH Coordinator Moderated by Job Satisfaction - Sarah Octavia; Ahmad (International Journal of Asian Business and Management, 2024)
This investigate points to portray and analyze the impact of Competency and stipend on the execution of the Family Trust Program (PKH) facilitator and to analyze work fulfillment in directing the impact of Competency and Emolument on the execution of the Family Trust Program (PKH) facilitator within the Kalimantan territorial zone. The irregularity between the comes about of past investigate was the inspiration for this investigate. In this investigate, the testing procedure utilized the Census technique, meaning that the complete populace was sampled, to be specific all the Family Trust Program Facilitators within the Kalimantan territorial region totaling 66 individuals. The information investigation strategy that will be utilized in this investigate is to utilize Auxiliary Condition Modeling and offers Way Explanatory capabilities. The way examination that will be utilized in this inquire about is Partial Slightest Squares (PLS), utilizing Smart-PLS. The examine comes approximately show up that competency consolidates a critical affect on the execution of the PKH facilitator, while emolument has no critical affect on execution, at that point the interaction between Competency and Compensation and work fulfillment has no affect and isn't critical on the execution of the Kalimantan regional PKH facilitator, and work fulfillment does not coordinate the affect of competence, stipend and execution specialist